A COMPARATIVE ANALYSIS OF AMERICAN AND CHINESE CULTURES ACROSS SIX DIMENSIONS - Winardi, Andreas (PUPIL: International Journal of Teaching, Education and Learning, 2024)
In our rapidly advancing global world, technology, transportation, and communication are evolving at an unprecedented pace. Consequently, it has become increasingly common for individuals to work and study in foreign countries. Those who choose to live abroad must possess adaptability and the ability to adjust, as the cultural landscapes of their destination countries can differ significantly from their countries of origin. Notably, individuals from the Eastern Hemisphere may experience stark cultural contrasts when transitioning from their native Eastern culture to a Western culture. This paper aims to compare the cultural dimensions of China, representing Eastern culture, with those of the USA, representing Western culture. The analysis employs Hofstede’s Value Survey Model (VSM, 2013) to evaluate six cultural dimensions. The results reveal striking differences between China and the USA in four dimensions: Power Distance Index (PDI), Individualism (IDV), Long-Term Orientation (LTO), and Indulgence (IDL). Conversely, the two countries exhibit similarities in the dimensions of Masculinity (MAS) and Uncertainty Avoidance (UAI).